Economic, digital, or entrepreneurial literacy: Which matters for driving students' economic behaviour? - B. S. Narmaditya; S. Sahid; M. Hussin (Russian State Vocational Pedagogical University, 2024)
Introduction. It remains a challenge for educational sides to confront the advancement of technology that has both challenges and opportunities in various sectors of human life. Since the matter of this theme, the studies on the impact of digital literacy and economic behaviour are insufficient. The lack of a broader understanding of the involvement of digital literacy in the economic and management literature with economic behaviour of students has motivated to perform a systematic literature review to identify and synthesise essential gaps in the literature. Despite there being several reviews in economic behaviour, it is not connected specifically to entrepreneurial literacy, and digital literacy. Most studies are taking a stance on investigating consumption behaviour or financial behaviour, as well as involving financial literacy as the major.Aim. This study aims to identify the interconnectedness between economic, entrepreneurial, and digital literacy and economic behaviour of students.Methodology and research methods. This study employed a systematic literature review of papers published in Scopus, Web of Science, EBSCOhost, and ProQuest databases using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The use of PRISMA is beneficial in providing more detail results and diminishing any possibility biases.Results and scientific novelty. The results of the study indicate that economic, digital, and entrepreneurial literacy can have impact to economic behaviour of students. The findings show an increasing economic behaviour trend in recent years in Indonesia and some countries. Thus, the study also noted that economic and digital literacy had been confirmed as essential to predict economic behaviour in terms of consumptive and productive activities. Meanwhile, the role of entrepreneurial literacy is paid less attention among scholars in explaining economic behaviour of students. This result will offer to future scholar in this theme to investigate these variables using certain method and approach.Practical significance. The results of this study provide a practical suggestion for scholars in the field of economics and entrepreneurship to consider the variables listed in this study. In addition, the study review synthesises several gaps research in the education, economics, and management literature that present a basis for providing future research related to economic behaviour.